2021
DOI: 10.5306/wjco.v12.i10.868
|View full text |Cite
|
Sign up to set email alerts
|

Human epidermal growth factor receptor 2 targeted therapy in endometrial cancer: Clinical and pathological perspectives

Abstract: Endometrial cancer is the most common gynecological cancer in developed countries, and its incidence has increased. The majority of patients with endometrial cancer have an early disease and favorable prognosis; however, a significant proportion of endometrial cancer, which mainly comprises high-grade or type II endometrial cancer such as serous, clear cell, and carcinosarcoma, shows advanced/recurrent disease and dismal prognosis. Novel therapeutic development is required for patients with aggressive endometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…ERK5 also participates in the proliferative signaling in response to activation of HER2 receptors in breast cancer cells, [ 40 ], and ERK5 inhibition sensitizes these cells to anti-HER2 treatments [ 41 ]. 20%-40% of patients with advanced non-endometrioid EC show HER2 overexpression [ 42 ], and Trastuzumab added to standard chemotherapy improved survival of patients with HER + aggressive serous EC, according to a recent phase 2 study [ 43 ]. Thus, it will be relevant to investigate whether ERK5 also mediates HER2 signaling in aggressive EC, and whether ERK5 inhibition could be of help to sensitize these cells to anti-HER2 therapies.…”
Section: Discussionmentioning
confidence: 99%
“…ERK5 also participates in the proliferative signaling in response to activation of HER2 receptors in breast cancer cells, [ 40 ], and ERK5 inhibition sensitizes these cells to anti-HER2 treatments [ 41 ]. 20%-40% of patients with advanced non-endometrioid EC show HER2 overexpression [ 42 ], and Trastuzumab added to standard chemotherapy improved survival of patients with HER + aggressive serous EC, according to a recent phase 2 study [ 43 ]. Thus, it will be relevant to investigate whether ERK5 also mediates HER2 signaling in aggressive EC, and whether ERK5 inhibition could be of help to sensitize these cells to anti-HER2 therapies.…”
Section: Discussionmentioning
confidence: 99%
“…ERK5 also participates in the proliferative signaling in response to activation of HER2 receptors in breast cancer cells, [33], and ERK5 inhibition sensitizes these cells to anti-HER2 treatments [34]. 20%-40% of patients with advanced non-endometrioid EC show HER2 overexpression [35], and Trastuzumab added to standard chemotherapy improved survival of patients with HER + aggressive serous EC, according to a recent phase 2 study [36]. Thus, it will be relevant to investigate whether ERK5 also mediates HER2 signaling in aggressive EC, and whether ERK5 inhibition could be of help to sensitize these cells to anti-HER2 therapies.…”
Section: Discussionmentioning
confidence: 99%
“…16 60 Human epidermal growth factor receptor 2/neu Human epidermal growth factor receptor 2 (HER2/neu) is a receptor tyrosine protein kinase (erbB-2) that is encoded by the ERBB2 gene and is overexpressed in roughly 20-60% of uterine serous carcinomas, 30-60% of uterine clear cell carcinomas, and offers a therapeutic target. 61 Trastuzumab is a humanised monoclonal antibody that targets HER2/neu, with demonstrated efficacy in other tumours with HER2/neu overexpression including breast and gastric cancers. 61 Initial evaluation in a phase 2 trial of 286 patients of single agent trastuzumab in advanced and recurrent endometrial cancer overexpressing HER2/neu showed no progression-free or overall survival benefit.…”
Section: Copy Number Highmentioning
confidence: 99%
“…61 Trastuzumab is a humanised monoclonal antibody that targets HER2/neu, with demonstrated efficacy in other tumours with HER2/neu overexpression including breast and gastric cancers. 61 Initial evaluation in a phase 2 trial of 286 patients of single agent trastuzumab in advanced and recurrent endometrial cancer overexpressing HER2/neu showed no progression-free or overall survival benefit. 62 However, trastuzumab in combination with standard-of-care carboplatin and paclitaxel in uterine serous carcinomas with HER2/neu overexpression has demonstrated efficacy.…”
Section: Copy Number Highmentioning
confidence: 99%